Os ilustres, prudentes e zelosos cidadãos baianos e a construção do Estado Nacional (1824-1831) - Oliveira, Nora de Cassia Gomes de (2007)
The changes that had happened in the workshop of the History, from the years of 1930, under the influence of the School of the Annales and the English Social History, and resulted in many possibilities of research in the most varied areas, including Political History that embarked on a renewal of its subjects, as well as others had been revisited under new perspectives. The new discussions on Politics History had contributed for this study that analyzes the construction of the State in Brazil, from the political relations between Bahia province and the central government, sited in Rio de Janeiro, during the years of 1824-1831, period when the Brazilian political autonomy, recently acquired, was tested by the game of the disputing forces. The surmounting of the divergences in terms of threat of territorial fragmentation and political instability, expressed by the provincial elites and population, in direction to a political order directed from the Court of Rio de Janeiro was analyzed from another place than that one established by the historiography on the subject called the Center-South. That is, thinking about the construction of the Brazilian National State, in this study, meant understanding the economical and political role of Bahia province to bring into effect the unitary and centralist project represented by D. Pedro I. Furthermore, to understand how the political elites acted in province in order to preserve the social order and stability. This task was a priority of the province s presidents, as well as of the local elite, more widely represented, since 1828, in the General Province Council. The Bahia support, even being from the institutionalized power, was not unrestricted, although it had been constitutional since 1821 and remained in this way until the end of Primeiro Reinado. However, when innumerable insurgencies from other social sectors, specially the militaries and the slaves, damaged the public calmness and menaced the property, it presented divergences. At this moment, for Bahia s elite, even its limited autonomy appears to be threatened both by the provincial context and the events in the Court. Thus, it was already possible to realize that the political-bureaucratic instances of the Brazilian State could be assumed by those who were born Brazilians, including a king born in the country, who would guarantee this elite s interests.